Efficient Energy Management and Grid Interconnection of Solar PV System - Mehta, Shivinder; Ilahi Bakhsh, Farhad; Neetan Sharma, Neetan (International Journal of Engineering and Technology, 2018)
With the increasing concerns on environment and increasing emission of greenhouse gases, we need to reduce the energy required to provide necessary products and services essential for ease of living by implementing efficient use of energy. Also we need to shift towards more clean and green forms of energy. Sun is the ultimate source of energy and its energy reaching at Earth's surface is about 10000 times greater than what we are consuming presently. Solar and wind remains in the top list of clean and green energy.Solar energy harnessed by Multifunctional photovoltaic converters (MPVC) are getting popular now a day as, it combines the advantages of inverters connected to the network (grid-tie inverter) and off-grid type inverter, as well as Uninterruptable Power Supplies (UPS). Grid tie inverter simply feeds the excess power generated to the grid with full utilization of solar panels.Â